Cross-cultural Adaptation of the Paediatric Epileptic Medication Self-Management Questionnaire (PEMSQ) in Malay Version - Nazmi Liana Azmi; Noor Haslina Othman; Anis Alfitrah Abdul Wahab; Foo Hui Shin; Mohamad Hisyam Hamzah; Nur Hidayah Ismail (Asian Journal of Medicine & Health Sciences, 2023)
Introduction: Effective self-management in children with epilepsy can optimize treatment efficacy and clinical outcomes, and reduce unnecessary healthcare utilization and costs. The Paediatric Epileptic Medication Self-Management Questionnaire (PEMSQ) for caregivers was developed by Modi et al. in 2010 to measure the elements of self-management in children newly diagnosed with epilepsy between the age of 2 to 14 years old. In this study, we attempted to cross-culturally adapt the PEMSQ into Malay as well as to determine its validity and reliability among caregivers of children with epilepsy. Materials and methods: Forward-backward translation was carried out by two groups of independent translators (experts in content and language). The content validation for the translated PEMSQ was performed by a panel of five experts with the cut-off point of 1.00, while the face validation was conducted among 10 targeted respondents with the threshold of 0.80. Finally, the reliability test was done in a pilot study amongst 65 caregivers of children with epilepsy with the minimum acceptable Cronbach’s alpha values of 0.60 and inter-item correlations of between 0.15 to 0.50. All data were analysed using Statistical Package for Social Sciences (SPSS) version 20. Results: The content validity indexes for all items were 1.00, indicating good relevancy. The face validity indexes were within the range of 0.80 to 1.00, suggesting that the questionnaire was easily understood by the targeted respondents. In the pilot study, the Cronbach's alpha coefficient of the overall questionnaire was calculated to be 0.877. All domains except for Belief about Medication Efficacy managed to score Cronbach’s alpha values of more than 0.60. The average inter-item correlations for all domains were within the range of 0.15 to 0.50, demonstrating acceptable internal consistency. Conclusion: The Malay version of the PEMSQ is found to be a valid and reliable self-administered questionnaire to measure self-management among caregivers of children between 2 and 14 years old with epilepsy. Further refinement of the research instrument can be considered, including confirmatory factor analysis.